THE PROMINENCE OF THE “SESLER” MAGAZINE FOR THE DEVELOPMENT OF TURKISH EDUCATION - Osman Emin (BAL-TAM Balkan Türkoloji Araştırmalar Merkezi, 2019)
It is known that Macedonia is one of the most complex region in the Balkans. Being regarded as the heart of the Balkans, according to the old historians,Macedonia is considered to be the holder of the attribute of a multinational state and the museum of race(ethnicity), even today is the holder of the attribute of a multinational state. Macedonia is a multilingual, multi – national and a zone noted for its mosaic of cultures. By the end of the 19th century,being seen in the fields of education,the pozitive development reached its end with the Balkan Wars. Banning the teaching of Turkish during the period of the World Wars, the Turkish education was drawn to a close.An application was commenced, headed for the prime at the hands of the new schools, skilled teachers, curricula, estimable instructors. In other words,after 4o years of break, the ban on Turkish education in the 1912, was barely given permission for further improvments on the Turkish education. The connection of Macedonia to the Federal Republic of Yugoslavia was ended with the declaration of independence on the 8th of September, 1991. From that date onwards, changes that came into view and after a certain number of constitutional changes, in 1991 with the reorganization act on education system several alterations were made on the education system of the Republic of Macedonia. From 1945 onwards, the Republic of Macedonia in its attempt in order to promote the Turkish education and the Turkish lectures, to determine the curricula changes and developments has published many reports and articles. Throughout the 1956 – 2001 being published at the “Sesler”magazine showed up the Turkısh education and training in what sort, in what manners its changes and developments has originated in the Republic of Macedonia, while being a member of the Socialist Federal Republic of Yugoslavia and starting from 1991 onwards even taking its place as an independent state in the international relations. During the period of Socialist Yugoslavia, the literary, social and community developments,were embraced at the magazine by articles right alongside the issues in the fields of education including the proposals for the resolution of the issues. Generally seen from this standpoint, the magazine “Sesler” in being the voice of the Macedonian Turks in the fields of education it clearly has become an indispensable part for the Turkish community.
Keywords: Macedonia, Turkish education, Sesler Magazine...